ANALISIS PENERAPAN SAK-EMKM, PERENCANAAN PAJAK, TINGKAT PENDIDIKAN, PEMAHAMAN AKUNTANSI, DAN PERSEPSI PELAKU USAHA ATAS TUJUAN LAPORAN KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PADA UMKM (Studi Empiris pada UMKM Industri Mebel di Bojonegoro) - Ika Widyaningrum; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
This study aims to determine the effect of the application of SAK-EMKM, tax planning, owner's education level, understanding of accounting, and perceptions of business actors on the purpose of financial statements on the quality of financial reports.This study uses the type of data obtained directly from the first party or can be called primary data. The population in this study is MSMEs that have been registered with the Cooperatives and SMEs Service Office. The sample used in this study was 100 business units with random sampling method as the method for taking the sample. Data was collected by distributing questionnaires to respondents. Analysis of the data used in this study is regression analysis using the SPSS 25 program.The results showed that the application of SAK-EMKM and tax planning had a positive and significant effect on the quality of financial reports. While the owner's education level, understanding of accounting, and perceptions of business actors on the purpose of financial statements do not have a positive and significant effect on the quality of financial reports.